3289 The Role of Suggestibility in Alcohol Use and Misuse. (27th March 2019) - Cowand, Alexandra; Stangl, Bethany L.; Schwandt, Melanie L.; Schneider, Alyssa; Gilman, Jodi M.; Diazgranados, Nancy; Ramchandani, Vijay A.
Abstract : OBJECTIVES/SPECIFIC AIMS: Suggestibility, defined as the inclination to accept and internalize messages, has not been assessed much in relation to alcohol use. Prior research has shown that suggestibility to social cues and peer influence may play a role in driving alcohol consumption. Our previous work has shown associations between suggestibility and alcohol consumption in social drinkers. This study aims to examine how suggestibility and social susceptibility are related to ideas alcohol consumption and consequences across the spectrum of alcohol use and misuse. We hypothesize that those with higher suggestibility and social susceptibility reports will also have higher alcohol consumption and consequences, and that the impact of susceptibility is lower in dependent compared to non-dependent drinkers. METHODS/STUDY POPULATION: Study participants enrolled in the NIAAA screening and assessment protocol (N=157) completed questionnaires on suggestibility and alcohol consumption, The Multidimensional Iowa Suggestibility Scale (MISS) is a 95-question self-report assessment of suggestibility which draws from subcategories of consumer suggestibility, perceivability, physiological suggestibility, physiological reactivity, and peer conformity. Alcohol measures included 90-day Timeline Followback interviews and the Alcohol Use Disorder Identification Test (AUDIT). Participants also underwent the Structured Clinical Interviews for DSM-IV or DSM-5 disorders, and were stratified into two groups: alcohol dependent (N = 86) and non-dependent (N=71). Median split by age was additionally used to explore age's relationship with suggestibility and alcohol with the under 36 (N = 45) and over 36 (N = 26) non-dependent groups. RESULTS/ANTICIPATED RESULTS: Initial analyses showed marked differences between the dependent and non-dependent groups in the relationship between the MISS total score and AUDIT total score. The non-dependent group showed significant positive correlations between MISS and AUDIT scores (r = 0.460, p < 0.001), while the dependent group did not show any correlation between MISS and AUDIT scores. Further examination of these relationships in the nondependent group revealed that MISS scores were also significantly positively correlated with AUDIT subscores of consumption, harm, and dependence. Age was found to have a significant negative correlation with MISS score (r = −0.354, p < 0.01). To better understand the role of age, the sample was split based on the median age (36 yrs), and analyzed separately. Results indicated robust relationships between MISS score and AUDIT (r = 0.457, p < 0.01) in the younger age group. In addition, the younger age group also showed significant relationships between MISS score and 90-day TLFB measures of total drinks, days drinking, and heavy drinking days. DISCUSSION/SIGNIFICANCE OF IMPACT: In non-dependent individuals, there was a significant positive relationship between suggestibility and alcohol measures, and these effects were amplified in younger individuals. No relationship was found between suggestibility and alcohol measures in the alcohol dependent individuals. This may be related to a greater impact of social and external contextual cues in younger social drinkers compared to dependent drinkers where tolerance and craving may have greater impact on alcohol consumption. These findings have important implications for traits that may put individuals at risk for developing harmful patterns of alcohol use and misuse. Future analyses will aim to examine biobehavioral underpinnings of the relationship between suggestibility and alcohol consumption.